Ecologia e biodiversidade de cupins (Insecta, Isoptera) em remanescentes de Mata Atlântica do nordeste brasileiro - Vasconcellos, Alexandre (2003)
Communities of termites in the Atlantic forest of Northeast Brazil were studied at four forest remnants, northern of the River São Francisco, namely: Reserva Biológica de Pedra Talhada (RPT), State of Alagoas; Horto Dois Irmãos (HDI), State of Pernambuco; Reserva Biológica Guaribas (RBG) and Mata do Buraquinho (MAB), both in the State of Paraíba. Several aspects of the ecology and natural history of these insects were analysed, with emphases on (i) their taxonomic and functional structures and seasonal influence on the diversity and richness of species at all localities (RPT, HDI, RGB, MAB); (ii) the abundance and biomass of populations in the RPT, HDI, and MAB; (iii) the participation of three species of Nasutitermes on removal of wood from the necromass in the HDI and MAB; (iv) the seasonal effects on abundance and biomass of termites on leaf litter, wood, soil, and tree trunks in the RBG; and (v) the abundance and spatial distribution of conspicuous nests at two sites with different successional stages in the RBG. In total, 61 species of termites were found, most of them of the family Termitidae (78,7%), followed by the families Kalotermitidae (14,7%) and Rhinotermitidae (6,6%). Ten species are reported here for the first time as occurring in the Atlantic forest. Among the identified species, 23 also occur in the Amazonian forest, showing that both biomes have similar termite fauna. The taxonomic and functional structures of the communities collected throughout the dry and rain seasons were quite similar, suggesting that the survey protocolo of termite biodiversity can be applied at any period of the year without altering drastically the communities structure. The abundance varied from 4951 to 5663 termites/m2 and biomas varied from 8,05 to 10,64g (fresh weight)/ m2. The termites were found mainly in the soil, 0-20 cm depth, and in dead wood. Two species were most abundant, Embiratermes parvirostris and Nasutitermes corniger. The average of wood consumption in laboratory of N. corniger, N. ephratae and N. macrocephalus was 9,43 mg (dry weight)  g of termite (fresh weight) -1  day-1. These three species alone remove from the HDI and MAB areas ca.67 and 73 g of wood  ha-1  year-1, respectively, which mean 2,9% and 3,3% of the total animal production of dead wood, respectively. However, 25 species of termites in the MAB and 21 in the HDI utilize wood as their nutrient source, suggesting that termites participation on removal of wood could be higher than 15% of the annual production. The quantitative sampling performed in the leaf litter, nests, soil, and tree trunks revealed large xv abundance and biomass of specimens of the subfamily Nasutitermitinae and of individuals of humus feeding group. The seasonal influence on the fauna of termites was only perceptible in nests and tree trunks, which appears to be related to the effects of one season on the production of wringed brood, foraging activity, and production of plant necromass. Eight termite species are conspicuous nest-builders in the studied areas, noticeably the abundant constructions built Microcerotermes exiguus and N. corniger. The spatial distribution of nests by each species and feeding groups was in the most cases at random, suggesting that competition does not represent an important determining factor of the spatial distribution pattern of nests. The analyses of abundance, taxonomic composition, and feeding groups of nest-builders species showed to be an additional tool for the evaluation of the habitat quality, indicating a more mature stage in the successional process.